PENGARUH PENGGUNAAN PENYALUT BIOBLEND PS/PCL TERHADAP PELEPASAN ZAT AKTIF UREA GRANUL - -, Salman; -, Febriyenti; Djamaan, Akmal (Universitas Andalas, 2015)
The most widely used surfactant is an anionic surfactant which is synthesized from petroleum namely Linear Alkylbenzene sulphonate (LABS). Methyl Ester Sulfonate which is currently being developed. Surfactant can produced from palm oil methyl ester via sulfonation sulfonate. When in this research using sodium metabisulphite. The aims of this work is to synthesize Methyl Ester Sulfonate surfactant from Palm Oil Methyl Ester using Sodium Metabisulphite and a catalyst Calcium Oxide. The effects of time and the mole ratio are also investigated. Sulfonation process carried out in 4, 5, 6 hours with mole ratio of 1: 0,5, 1:1, 1: 1,5, temperature of 80Â° C and with stirring speed of 450 rpm. It haven been found that the surfactant produced has density of (0.89490 g/cm3 - 0.89545 g/cm3), viscosity (2.0323 cP - 2.1329 cP), pH (2,03 - 2,48), surface tension (32.60 mN/m - 33.60 mN/m), interfacial tension (30.45 mN/m - 30.94 mN/m), and the stability emulsion (59.17% - 89, 17%).